Cuentas por cobrar: impuestos, tasas y contribuciones del GAD Municipal de Palenque en el periodo 2023. - Valero Aguirre, Geanella Noemi (2024)
The case study "Accounts Receivable: Taxes, Fees, and Contributions of the Municipal GAD of Palenque in the period 2023" investigates the management of these accounts in the Autonomous Decentralized Government (GAD) of Palenque, Ecuador. Its general objective is to determine the management of accounts receivable using financial tools to evaluate their impact on the 2023 budget. The methodology includes interviews with the staff of the Revenue Department and the mayor of the Municipal GAD, as well as an analysis of the financial statements. The policies for recording and collecting accounts, internal procedures and controls, and the challenges in managing these accounts were examined. The results of the analysis of accounts receivable between 2022 and 2023 showed a decrease in collection, suggesting problems in the administration of these revenues. This reduction affected the liquidity of the Municipal GAD, compromising its ability to meet financial obligations and carry out essential projects. The study's conclusions indicate that current accounting policies are insufficient and require improvement. It is recommended to develop clear and uniform accounting policies, strengthen internal controls, and train the staff of the Revenue Department in better accounting practices. Additionally, it is suggested to improve the methods of recording and tracking accounts receivable by updating financial systems and implementing regular audits. Finally, the importance of fostering a culture of tax compliance and citizen participation through educational campaigns and incentive programs is highlighted. Establishing mechanisms of collaboration between the municipality and the community is crucial to improving the management and collection of municipal revenues.